Topics in Numerical Partial Differential Equations and Scientific Computing - Brenner, Susanne C. (The IMA Volumes in Mathematics and its Applications,, 2016)
Numerical partial differential equations (PDEs) are an important part of numerical simulation, the third component of the modern methodology for science and engineering, besides the traditional theory and experiment. This volume contains papers that originated with the collaborative research of the teams that participated in the IMA Workshop for Women in Applied Mathematics: Numerical Partial Differential Equations and Scientific Computing in August 2014.